Effect of Bronchoscopist-Directed Sedation and Other Factors on Patient Comfort during Diagnostic Flexible Bronchoscopy - Rahul Magazine; Keerthi Nedumala Sisupalan; Vyshak Uddur Surendra; Bharti Chogtu; Preetam Rajgopal Acharya; Vasudeva Guddattu (Scientifica)
Background. The factors affecting patient comfort during flexible bronchoscopy are not sufficiently addressed in resource-limited countries, and a need to devise strategies to improve patient experience is felt. The present study was undertaken to assess the effect of sedation and other factors on patient comfort during flexible bronchoscopy. Methods. A total of 374 patients, aged ≥18 years undergoing flexible bronchoscopy, were enrolled in this prospective, single-center, cross-sectional study. The baseline clinical data of sedation and nonsedation groups were recorded. Anxiety level was assessed using Visual Analog Scale (VAS). Postprocedure VAS score (primary outcome measure) assessed the discomfort related to flexible bronchoscopy. Patient-reported willingness for a repeat procedure and occurrence of adverse events were used as secondary outcome measures. Based on the median of VAS score, the study population was divided into low discomfort and high discomfort groups, and the factors affecting comfort levels in these two groups were noted. Results. Postprocedural VAS score (median (Q1, Q3)) for sedation and nonsedation groups was 20 (15, 30) and 25 (20, 40), respectively (<0.001). Willingness for a repeat procedure was significantly more in the sedation group (p=0.002). In the low and high discomfort groups, the preprocedural anxiety level (median (Q1, Q3)) was 20 (10, 25) and 30 (20, 40), respectively (p<0.001). Conclusion. Bronchoscopist-directed sedation significantly reduces patient discomfort and increases their willingness for a repeat procedure. Midazolam-fentanyl combination and lower prebronchoscopy anxiety are associated with lower discomfort levels during flexible bronchoscopy. This study is registered with the Clinical Trial Registry of India (CTRI/2018/11/016328).